Changes in critical velocity and critical stroke rate during a 12 week swimming training period: A case study - Marinho, D. A.; Silva, A. J.; Reis, V. M.; Costa, A. M.; Brito, J. P.; Ferraz, R.; Marques, M. C. (Journal of Human Sport & Exercise, 2009)
The aim of this study was to analyse the evolution of critical velocity and critical stroke rate during 12 weeks of training in age group swimmers. Fourteen age group male swimmers took part in this investigation. The evaluation took place in two different trials. The first one was conducted at the beginning of the season and the second one after 12 weeks of training. For each subject the critical velocity and the critical stroke rate were determined in both trials. The main result was that critical velocity increased, whereas critical stroke rate decreased between the first and second trials. It seems that technical ability was improved during the 12 weeks of training. The swimmers were able to perform at the same physiological intensity at higher velocities and with less stroke rate. This information could help swimming coaches monitoring their training without expensive instruments.